Evaluasi Program Sekolah Ramah Anak di SMPN 3 Narmada Menggunakan Model CIPP (Context, Input, Prosess, dan Product) - Zakiyyatun Humairah (Mataram University, 2026)
This study aims to evaluate the implementation of the Child-Friendly School Program at SMPN 3 Narmada using the CIPP evaluation model, which includes the components of context, input, process, and product. This study is an evaluative study with a descriptive approach, which uses data collection techniques in the form of observation, interviews, and documentation studies. The data obtained are analyzed through the stages of data reduction, data presentation, and drawing conclusions by applying triangulation of sources and methods to ensure data validity. The results of the study indicate that in terms of context, the Child-Friendly School Program has been in accordance with the needs and characteristics of the school. In terms of input, the availability of resources has generally supported the program implementation although there are still limitations in some facilities. In terms of process, the program implementation is running well, but not all Child-Friendly School policies are implemented consistently. In terms of product, the program has a positive impact on creating a safe and comfortable school environment and increasing parental participation, although the healthy environment aspect still needs to be improved. Overall, the Child-Friendly School Program at SMPN 3 Narmada is considered worthy of being continued with improvements in several supporting aspects.